Deterministic and Efficient Interactive Coding from Hard-to-Decode Tree Codes - Brakerski, Zvika; Kalai, Yael Tauman; Saxena, Raghuvansh (FOCS 2020, 2020)
The field of Interactive Coding studies how an interactive protocol can be made resilient to channel errors. Even though this field has received abundant attention since Schulman's seminal paper (FOCS 92), constructing interactive coding schemes that are both deterministic and efficient, and at the same time resilient to adversarial errors (with constant information and error rates), remains an elusive open problem. An appealing approach towards resolving this problem is to show efficiently encodable and decodable constructions of a combinatorial object called tree codes (Schulman, STOC 93). After a lot of effort in this direction, the current state of the art has deterministic constructions of tree codes that are efficiently encodable but require a logarithmic (instead of constant) alphabet (Cohen, Haeupler, and Schulman, STOC 18). However, we still lack (even heuristic) candidate constructions that are efficiently decodable. In this work, we show that tree codes that are efficiently encodable, [but not efficiently decodable], also imply deterministic and efficient interactive coding schemes that are resilient to adversarial errors. Our result immediately implies a deterministic and efficient interactive coding scheme with a logarithmic alphabet (i.e., 1loglog rate). We show this result using a novel implementation of hashing through deterministic tree codes that is powerful enough to yield interactive coding schemes.